2016
DOI: 10.1186/s12933-016-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of inducible NO synthase by exogenous adenosine in vascular smooth muscle cells activated by inflammatory stimuli in experimental diabetes

Abstract: BackgroundAdenosine has been shown to induce nitric oxide (NO) production via inducible NO synthase (iNOS) activation in vascular smooth muscle cells (VSMCs). Although this is interpreted as a beneficial vasodilating pathway in vaso-occlusive disorders, iNOS is also involved in diabetic vascular dysfunction. Because the turnover of and the potential to modulate iNOS by adenosine in experimental diabetes have not been explored, we hypothesized that both the adenosine system and control of iNOS function are impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Previous researchers documented that LPS activates the excess production of NO via upregulation of iNOS as detected in the present study and by others Zhang et al 2016;Wei et al 2017). Another study reported that the iNOS gene is a highly inducible gene and its transcription is readily upregulated by inflammatory cytokines (Nassi et al 2016). Excess cytokines production might be caused by the LPS ability to stimulate mitogen activated protein kinase (MAPK) (Peng et al 2016) and NF-κB (Jang et al 2017) pathways.…”
Section: Immunohistochemical Assessment Of Inossupporting
confidence: 73%
“…Previous researchers documented that LPS activates the excess production of NO via upregulation of iNOS as detected in the present study and by others Zhang et al 2016;Wei et al 2017). Another study reported that the iNOS gene is a highly inducible gene and its transcription is readily upregulated by inflammatory cytokines (Nassi et al 2016). Excess cytokines production might be caused by the LPS ability to stimulate mitogen activated protein kinase (MAPK) (Peng et al 2016) and NF-κB (Jang et al 2017) pathways.…”
Section: Immunohistochemical Assessment Of Inossupporting
confidence: 73%
“…Inflammatory also play an important role in the development of vascular damage associated to hyperglycemia [ 31 , 32 ]. During inflammation, inducible nitric oxide synthase activation generates an overabundance of NO in the circulation and induced the cardiovascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Activated macrophages are a significant source [ [4] , [5] , [6] ] but other cells also generate •NO, albeit at lower levels, via the constitutive enzymes eNOS and nNOS, and can therefore contribute to the flux of ONOOH formed in vivo . The presence of NOS isoforms in vascular smooth muscle cells is controversial [ [55] , [56] , [57] , [58] , [59] ]. Whilst there are considerable data consistent with iNOS expression on exposure of these cells to injury or cytokines this isoform, and also the endothelial isoform (eNOS), do not appear to be endogenously expressed in vascular smooth muscle cells [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%